Laminate and resin molded article comprising same
By forming a hard coating by laminating a curable resin composition of urethane acrylate resin and hindered amine light stabilizer onto an acrylic resin film, the problems of insufficient flexibility and weather resistance of acrylic resin films are solved, and high transparency, surface hardness and good secondary molding properties are achieved.
Patent Information
- Application Number
- CN202480020857.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-03-30
- Filing Date
- 2024-03-14
- Publication Date
- 2025-11-11
Smart Images

Figure CN120936661A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to laminates comprising acrylic resin films and resin molded articles comprising the same. Background Technology
[0002] Acrylic resin films are widely used for surface protection and / or coloring and decoration in various applications such as automotive interior and exterior materials, optical components, home appliance components, building exterior materials, and retroreflective materials due to their excellent transparency, weather resistance, high formability (able to be laminated to the surface of planar and / or three-dimensional substrates), good adhesion to other substrates, and printability. Furthermore, when applying acrylic resin films to these applications, hard coatings are often incorporated to further improve surface hardness, scratch resistance, and chemical resistance to various solvents and pharmaceuticals. For example, Patent Document 1 describes a hard coating film comprising a substrate made of an acrylic resin film and a hard coating composed of an electron beam cured resin composition containing an electron beam cured resin and a triazine-based ultraviolet absorber. In addition, Patent Document 2 describes a laminate comprising an acrylic resin film and a hard coating layer laminated on at least one side of the acrylic resin film, the hard coating layer comprising urethane acrylate resin, wherein the laminate has a crack elongation of 80% or more at 120°C.
[0003] Existing technical documents
[0004] Patent documents
[0005] Patent Document 1: Japanese Patent Application Publication No. 2012-207120
[0006] Patent Document 2: International Publication No. 2022 / 185815 Summary of the Invention
[0007] However, in the hard coating film with a hard coating layer on an acrylic resin film as described in Patent Document 1, the high degree of cross-linking of the hard coating layer hinders the flexibility of the acrylic resin film, resulting in poor secondary molding properties. Therefore, there is a problem that the shape on which the hard coating film can be laminated is limited. In addition, in the case of the laminate described in Patent Document 2, for example in the interior and exterior trim of automobiles, the long-term weather resistance may not be sufficient for applications involving sunlight exposure or exposure to wind and rain, and further improvement is needed.
[0008] The present invention was made in view of the above-mentioned problems, and provides a laminate with good transparency, surface hardness and chemical resistance, high secondary molding ability, excellent long-term weather resistance, and can be used for surface protection of resin molded articles with planar and / or three-dimensional surfaces, and a resin molded article containing the laminate.
[0009] One or more embodiments of the present invention relate to a laminate comprising an acrylic resin film and a hard coating layer laminated on at least one side of the acrylic resin film, wherein the acrylic resin film has a tensile elongation at break of 200% or more at 120°C, and the hard coating layer is formed from a cured resin composition comprising a urethane acrylate resin and a hindered amine light stabilizer having reactive functional groups, wherein the laminate has a tensile crack elongation at break of 100% or more at 120°C.
[0010] One or more embodiments of the present invention relate to a resin molded body comprising the above-described laminate and a thermoplastic resin substrate, wherein at least a portion of the thermoplastic resin substrate is covered by the laminate configured such that an acrylic resin film is on the thermoplastic resin substrate side.
[0011] According to the present invention, a laminate with good transparency, surface hardness and chemical resistance, high re-molding ability and excellent long-term weather resistance is provided, which can be used for surface protection of resin molded articles with planar and / or three-dimensional surfaces, and a resin molded article containing the laminate is provided. Attached Figure Description
[0012] Figure 1 This is a schematic cross-sectional view of a laminated body according to one embodiment of the present invention. Detailed Implementation
[0013] The inventors of this invention conducted in-depth research to solve the above-mentioned problems. Surprisingly, in laminates comprising an acrylic resin film and a hard coating, the use of an acrylic resin film with specific properties, and the formation of a hard coating from a cured product of a specific curable resin composition comprising a urethane acrylate resin and a hindered amine light stabilizer with reactive functional groups, resulted in laminates exhibiting good transparency, surface hardness, and chemical resistance, as well as improved secondary molding properties and long-term weather resistance.
[0014] Specifically, the laminates of one or more embodiments of the present invention exhibit a tensile crack elongation of 100% or more at 120°C and high re-formability, making them suitable for molded bodies, for example, having curved and / or three-dimensional shapes. Furthermore, the laminates of one or more embodiments of the present invention form a hard coating from a cured product of a specific curable resin composition comprising a urethane acrylate resin and a hindered amine light stabilizer having reactive functional groups, thereby improving long-term weather resistance. In particular, the laminates of one or more preferred embodiments of the present invention do not exhibit surface cracking of the hard coating even under accelerated weathering tests (hereinafter also referred to as "accelerated weathering tests"), where the laminate is positioned with the hard coating side as the light source, using a xenon lamp as the light source, and an irradiance of 180 W / m².2 Under conditions of (300-400nm), 1000 cycles (totaling 2000 hours) were performed, consisting of step 1 with an exposure time of 102 minutes, a black panel temperature of 60±3℃, a relative humidity of 65±5% and no rainfall, and step 2 with an exposure time of 18 minutes, a tank temperature of 38±3℃, a relative humidity of 95±5% and rainfall.
[0015] In this specification, when a numerical range is represented by "~", the numerical range includes both ends (upper and lower limits). For example, the numerical range "X~Y" includes both ends of X and Y, and is the same range as "above X and below Y". Furthermore, any number within this range and any range contained within this range are specifically disclosed. Additionally, when multiple numerical ranges are described in this specification, a numerical range obtained by appropriately combining the upper and lower limits of different numerical ranges is included.
[0016] (Acrylic resin film)
[0017] Acrylic resin films exhibit a tensile elongation at break exceeding 200% at 120°C. Consequently, the tensile crack elongation at 120°C is high in laminates with hard coatings, and the secondary molding properties of the laminates become readily available. There is no specific upper limit to the tensile elongation at break of acrylic resin films at 120°C.
[0018] The composition of an acrylic resin film is not particularly limited as long as its elongation at break at 120°C is 200% or more, but it is preferably formed from an acrylic resin composition containing acrylic resin and graft copolymer particles containing rubber components (also known as crosslinked elastomers).
[0019] <Acrylic Resin>
[0020] As the acrylic resin, conventionally known acrylic resins can be appropriately used. For example, from the viewpoint of hardness and moldability, when the total amount of the constituent units of the acrylic resin is set to 100% by mass, it is preferable to use an acrylic resin (also known as a thermoplastic acrylic polymer) composed of 50 to 100% by mass of methyl methacrylate units and 0 to 50% by mass of other constituent units. It should be noted that the total amount of methyl methacrylate units and other constituent units in the thermoplastic acrylic polymer is 100% by mass.
[0021] Other constituent units may include, for example, those derived from acrylic acid, acrylic acid derivatives, methacrylic acid, methacrylic acid derivatives, aromatic vinyl derivatives, and vinyl cyanide derivatives. Other constituent units may be glutarimide structures, lactone ring structures, N-substituted maleimide structures, and unsubstituted maleimide structures, as described later. Acrylic resins may contain one or a combination of two or more other constituent units.
[0022] Examples of acrylic acid derivatives include, but are not limited to, methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, isobutyl acrylate, cyclohexyl acrylate, 2-hydroxyethyl acrylate, 2-phenoxyethyl acrylate, benzyl acrylate, and glycidyl acrylate.
[0023] Examples of methacrylic acid derivatives include ethyl methacrylate, n-propyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, phenyl methacrylate, benzyl methacrylate, cyclohexyl methacrylate, 2-phenoxyethyl methacrylate, and isobornyl methacrylate, as well as reactive ultraviolet absorbers described later, but are not limited to these.
[0024] Examples of aromatic vinyl derivatives include, but are not limited to, styrene, vinyltoluene, and α-methylstyrene.
[0025] Examples of vinyl cyanide derivatives include acrylonitrile and methacrylonitrile, but are not limited to them.
[0026] To improve the heat resistance, rigidity, and surface hardness of acrylic resins, specific structural units can be introduced into the acrylic resins through copolymerization, functional group modification, and other methods. Examples of such specific structures include glutarimide structures as shown in Japanese Patent Application Publication Nos. 62-89705, 02-178310, and WO2005 / 54311; lactone ring structures as shown in Japanese Patent Application Publication Nos. 2004-168882 and 2006-171464; glutaric anhydride structures obtained by thermal condensation cyclization of (meth)acrylic acid units as shown in Japanese Patent Application Publication No. 2004-307834; maleic anhydride structures as shown in Japanese Patent Application Publication No. 5-119217; and N-substituted and unsubstituted maleimide structures as shown in WO2009 / 84541. For example, by introducing these structures into acrylic resins, the molecular chains become rigid. As a result, improvements such as increased heat resistance, increased surface hardness, reduced heat shrinkage, and improved chemical resistance can be expected.
[0027] There are no particular limitations on the manufacturing method of acrylic resins. For example, well-known polymerization methods such as suspension polymerization, bulk polymerization, solution polymerization, and emulsion polymerization can be used. In addition, well-known free radical polymerization, living free radical polymerization, anionic polymerization, and cationic polymerization can also be applied.
[0028] In 100% by weight of the acrylic resin film, the content of acrylic resin can be 20-100% by weight, preferably 20-99% by weight, more preferably 25-95% by weight, and even more preferably 30-90% by weight.
[0029] <Graft copolymers containing rubber components>
[0030] The acrylic resin membrane preferably contains graft copolymer particles (A) with an average particle size of 20-200 nm as graft copolymer particles containing a rubber component. In this case, the graft copolymer particles (A) are preferably dispersed in the acrylic resin or a matrix containing the acrylic resin and other components in the acrylic resin membrane. Alternatively, in addition to the graft copolymer particles (A), the acrylic resin membrane may, if necessary, contain graft copolymer particles (B) with an average particle size larger than that of the graft copolymer particles (A). In this case, both graft copolymer particles (A) and graft copolymer particles (B) are preferably dispersed in the acrylic resin or a matrix containing the acrylic resin and other components in the acrylic resin membrane.
[0031] The graft copolymer particles (A) preferably have a core-shell structure (multilayer structure) having a crosslinked elastomer (A1) as a rubber component and a graft polymer layer (A2) located on the surface side of the crosslinked elastomer (A1).
[0032] The crosslinked elastomer (A1) can be any known crosslinked elastomer. Preferably, the crosslinked elastomer (A1) is an acrylate-based crosslinked elastomer (a crosslinked elastomer composed of a polymer with acrylate as the main component). In this specification, "main component" refers to a component with a content of 50% by mass or more.
[0033] The particles of the acrylate-based crosslinked elastomer (A1) can have a concentric spherical multilayer structure in which a rigid or semi-rigid crosslinked resin layer is present inside the crosslinked elastomer layer. Examples of such rigid or semi-rigid crosslinked resin layers include rigid crosslinked methacrylate resin particles as shown in Japanese Patent Publication No. 55-27576, semi-rigid crosslinked particles composed of methyl methacrylate, acrylate, and styrene as shown in Japanese Patent Application Publication No. 4-270751, and crosslinked rubber particles with a high degree of crosslinking. By having such a rigid or semi-rigid crosslinked resin layer, improvements in transparency and color tone can sometimes be expected.
[0034] The graft copolymer particles (A) preferably have a core-shell structure formed by grafting a mixture of monomers that form a graft polymer layer (A2) in the presence of the aforementioned acrylate-based crosslinked elastomer (A1) particles.
[0035] The average particle size of the graft copolymer particles (A) should be 20–200 nm, preferably 50–150 nm, and particularly preferably 50–120 nm. When the average particle size of the graft copolymer particles (A) is too small, the impact resistance and flexural breakage resistance of the acrylic resin film tend to decrease. When the average particle size of the graft copolymer particles (A) is too large, the transparency of the acrylic resin film tends to deteriorate, and it tends to easily cause whitening due to bending.
[0036] As an acrylate-based crosslinked elastomer (A1), it is preferable to use crosslinked elastomer particles obtained by polymerizing a monomer mixture (a-1) comprising (a) acrylate, (b) a multifunctional monomer capable of copolymerizing with acrylate and having two or more non-conjugated double bonds per molecule, and (c) other vinyl monomers capable of copolymerizing with acrylate in any way.
[0037] Acrylates, other vinyl monomers, and multifunctional monomers can be mixed entirely and polymerized in a single-stage polymerization. Alternatively, to adjust the toughness, whitening resistance, etc., of acrylic resin films, the composition of the acrylates, other vinyl monomers, and multifunctional monomers can be appropriately modified, or, with the same composition, the acrylates, other vinyl monomers, and multifunctional monomers can be polymerized in two or more stages for multi-stage polymerization.
[0038] From the viewpoint of excellent polymerizability, low cost, and providing polymers with low Tg, aliphatic esters of acrylic acid are preferred as acrylates, alkyl acrylates are more preferred, and alkyl acrylates with alkyl groups having 1 to 22 carbon atoms are particularly preferred. The alkyl group can include any structure among straight-chain, branched, and cyclic (also called alicyclic) structures.
[0039] Specific examples of preferred alkyl acrylates include methyl acrylate, ethyl acrylate, propyl acrylate, n-butyl acrylate, isobutyl acrylate, 2-ethylhexyl acrylate, n-octyl acrylate, isobornyl acrylate, cyclohexyl acrylate, dodecyl acrylate, stearyl acrylate, heptadecanyl acrylate, and octadecyl acrylate. They may be used individually or in combination of two or more.
[0040] In 100% by mass of the monomer mixture (a-1), the amount of acrylate (preferably alkyl acrylate, more preferably alkyl acrylate with 1 to 22 carbon atoms in the alkyl group) is preferably 50 to 99.9% by mass, more preferably 70 to 99% by mass, and most preferably 80 to 99% by mass. If the amount of acrylate is 50% by mass or more, the acrylic resin film has good impact resistance and elongation at tensile break, and is less prone to cracking during secondary molding.
[0041] Other vinyl monomers include, for example, methyl methacrylate, ethyl methacrylate, propyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, phenyl methacrylate, benzyl methacrylate, cyclohexyl methacrylate, phenoxyethyl methacrylate, isobornyl methacrylate, and dicyclopentenyl methacrylate; vinyl cyanide derivatives such as acrylonitrile and methacrylonitrile; aromatic vinyl derivatives such as styrene, vinyltoluene, and α-methylstyrene; acrylic acid; acrylic acid derivatives such as β-hydroxyethyl acrylate, phenoxyethyl acrylate, benzyl acrylate, and glycidyl acrylate; methacrylic acid; methacrylic acid derivatives such as β-hydroxyethyl methacrylate, dimethylaminoethyl methacrylate, and glycidyl methacrylate; maleic anhydride; and maleic acid derivatives such as N-alkylmaleimide and N-phenylmaleimide. They can be used alone or in combination of two or more. From the viewpoint of weather resistance and transparency, monomers selected from methacrylates and aromatic vinyl derivatives are particularly preferred as other vinyl monomers.
[0042] In the monomer mixture (a-1) 100% by mass, the amount of other vinyl monomers is preferably 0 to 49.9% by mass, more preferably 0 to 30% by mass, and even more preferably 0 to 20% by mass. If the amount of other vinyl monomers exceeds 49.9% by mass, the impact resistance of the acrylic resin film may be reduced, the elongation at tensile fracture may be reduced, and cracks may easily occur during secondary molding.
[0043] As multifunctional monomers, monomers commonly used as crosslinking agents and / or grafting agents are preferred. Examples of multifunctional monomers that can be used include allyl methacrylate, allyl acrylate, triallyl cyanurate, triallyl isocyanurate, diallyl phthalate, diallyl maleate, divinyl adipate, divinylbenzene, ethylene glycol dimethacrylate, propylene glycol dimethacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, trimethylolpropane trimethacrylate, polyethylene glycol dimethacrylate, and dipropylene glycol dimethacrylate. These multifunctional monomers can be used alone or in combination of two or more.
[0044] As multifunctional monomers, those functioning as grafting crosslinkers are more preferred because they increase the number of graft bonds between the graft polymer layer (A2) and the crosslinked elastomer (A1), resulting in better dispersibility of the graft copolymer particles (A) in the acrylic resin, improved crack resistance to tensile and flexural deformation relative to the acrylic resin film, and reduced stress whitening. Among these multifunctional monomers, allyl methacrylate, allyl acrylate, triallyl cyanurate, triallyl isocyanurate, diallyl phthalate, and diallyl maleate, etc., allyl groups are preferred, with allyl methacrylate and allyl acrylate being particularly preferred.
[0045] In 100% by mass of the monomer mixture (a-1), the amount of the multifunctional monomer is preferably 0.1 to 10% by mass, more preferably 1.0 to 4% by mass. If the amount of the multifunctional monomer is within the above range, it is preferred from the viewpoint of the acrylic resin film's resistance to flexural breakage and flexural whitening, and the resin's flowability during molding.
[0046] In acrylate-based crosslinked elastomers (A1), to improve the grafting efficiency of the graft polymer layer (A2) described later, the amount of multifunctional monomers can be varied both inside and near the surface of the crosslinked elastomer (A1). Specifically, as shown in Japanese Patent No. 1460364 and Japanese Patent No. 1786959, by increasing the content of multifunctional monomers that function as grafting crosslinking agents near the surface of the crosslinked elastomer (A1) compared to its interior, the coating of the graft polymer layer of the graft copolymer particles (A) can be improved, resulting in better dispersibility in the acrylic resin, or suppressing the reduction in crack resistance caused by the peeling of the graft copolymer particles (A) from the acrylic resin interface. Furthermore, since sufficient coating can be achieved using a relatively small amount of graft polymer layer (A2), the amount of graft copolymer particles (A) used to introduce a specified amount of crosslinked elastomer (A1) into the acrylic resin composition can be reduced. Therefore, the melt viscosity of the acrylic resin composition can be reduced, and improvements in melt processability, film processing precision, and surface hardness of the acrylic resin film can be expected.
[0047] For purposes such as controlling the molecular weight and crosslinking density of the acrylate-based crosslinked elastomer (A1), and controlling thermal stability by reducing the double bond ends of the polymer during the disproportionation termination reaction accompanying polymerization, a chain transfer agent may be used in addition to the monomer mixture (a-1). The chain transfer agent can be selected from those commonly used in free radical polymerization. Examples of preferred chain transfer agents include monofunctional or polyfunctional thiols with 2 to 20 carbon atoms, such as n-octylthiol, n-dodecylthiol, and tert-dodecylthiol; mercapto acids; thiophenols; carbon tetrachloride; or mixtures thereof. The amount of chain transfer agent added is preferably 0 to 1.0 parts by mass, more preferably 0 to 0.2 parts by mass, relative to 100 parts by mass of the monomer mixture (a-1).
[0048] The particles of the crosslinked elastomer (A1) can be a single layer composed of the above-mentioned acrylate-based crosslinked elastomer (A1), or a multilayer structure comprising two or more layers composed of the above-mentioned acrylate-based crosslinked elastomer (A1).
[0049] The particles of the crosslinked elastomer (A1) may also include an acrylate-based crosslinked elastomer (A1) in at least one layer of a multilayer of particles comprising a rigid or semi-rigid crosslinked resin layer. Examples of monomers constituting the rigid or semi-rigid crosslinked resin layer include methacrylates such as methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, benzyl methacrylate, and phenoxyethyl methacrylate; alkyl acrylates such as methyl acrylate, ethyl acrylate, propyl acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, 2-ethylhexyl acrylate, and n-octyl acrylate; aromatic vinyl derivatives such as styrene and α-methylstyrene; vinyl cyanide derivatives such as acrylonitrile; maleic anhydride; maleic acid derivatives such as maleimides; and polyfunctional monomers having two or more non-conjugated double bonds per molecule. As a polyfunctional monomer, the same multifunctional monomers used in the polymerization of the acrylate-based crosslinked elastomer (A1) layer may be used. These monomers are particularly preferably selected from one or more of methyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, styrene, and acrylonitrile. Furthermore, during the polymerization of rigid or semi-rigid crosslinked resin layers, in addition to these monomers, a chain transfer agent may be used for purposes such as controlling the crosslinking density and controlling thermal stability by reducing the double bond ends of the polymer. The same chain transfer agent used in the polymerization of acrylate-based crosslinked elastomer (A1) layers can be used. The amount of chain transfer agent added is preferably 0 to 2 parts by mass, more preferably 0 to 0.5 parts by mass, relative to 100 parts by mass of the monomer mixture constituting the rigid or semi-rigid crosslinked resin layer.
[0050] When the graft copolymer particle (A) is a two-layer structure consisting of a crosslinked elastomer (A1) as the core particle and a graft polymer layer (A2), the graft copolymer particle (A) is typically obtained by graft copolymerizing a monomer mixture (a-2) containing 50-100% by mass of methacrylate and 0-50% by mass of other vinyl monomers that can copolymerize with methacrylate (wherein the total of methacrylate and other vinyl monomers is 100% by mass) in the presence of the crosslinked elastomer (A1) to form the graft polymer layer (A2).
[0051] From the viewpoints of (a) ensuring compatibility with the acrylic resin as the matrix, and (b) suppressing the reduction in film toughness caused by solvent impregnation during coating on the acrylic resin film, as well as whitening and cracking caused by stretching during molding, the amount of methacrylate in 100% by mass of the monomer mixture (a-2) is preferably 60% by mass or more, more preferably 80% by mass or more, further preferably 90% by mass or more, and particularly preferably 97% by mass or more.
[0052] In the monomer mixture (a-2), examples of methyl methacrylates include ethyl methacrylate, propyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, hexyl methacrylate, cyclohexyl methacrylate, 2-ethylhexyl methacrylate, octyl methacrylate, phenyl methacrylate, and benzyl methacrylate, among other alkyl methacrylates. Alkyl methacrylates with 1 to 4 carbon atoms in the alkyl group are preferred.
[0053] In the monomer mixture (a-2), alkyl acrylates with 2 or more carbon atoms in the alkyl group can be used as other vinyl monomers. The alkyl acrylates with 2 or more carbon atoms in the alkyl group are preferably selected from one or more of ethyl acrylate, propyl acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, hexyl acrylate, cyclohexyl acrylate, octyl acrylate, dodecyl acrylate, and stearyl acrylate; more preferably from one or more of ethyl acrylate, n-butyl acrylate, isobutyl acrylate, and tert-butyl acrylate; and particularly preferably n-butyl acrylate.
[0054] In the monomer mixture (a-2), other vinyl monomers may also be used, such as aromatic vinyl derivatives of styrene and its nucleated derivatives, vinyl cyanide derivatives of acrylonitrile, methacrylic acid and its derivatives, acrylic acid and its derivatives, N-substituted maleimides, maleic anhydride, methacrylamide and acrylamide, etc.
[0055] The monomer mixture (a-2) preferably includes a reactive ultraviolet absorber as another vinyl monomer. That is, the graft polymer layer (A2) preferably includes constituent units derived from the reactive ultraviolet absorber. When the monomer mixture (a-2) includes a reactive ultraviolet absorber, it is easy to obtain an acrylic resin film with good weather resistance and chemical resistance.
[0056] As a reactive ultraviolet absorber, any known reactive ultraviolet absorber can be used, without particular limitation. From the viewpoint of the molding processability and weather resistance of acrylic resin films, compounds represented by the following general formula (1) are preferred as reactive ultraviolet absorbers.
[0057]
[0058] In general formula (1), X is a hydrogen atom or a halogen atom, R1 is a hydrogen atom, a methyl group or a tertiary alkyl group with 4 to 6 carbon atoms, R2 is a straight-chain or branched alkylene group with 2 to 10 carbon atoms, and R3 is a hydrogen atom or a methyl group.
[0059] As reactive ultraviolet absorbers represented by general formula (1), examples include 2-(2'-hydroxy-5'-(meth)acryloyloxyethylphenyl)-2H-benzotriazoles, and more specifically, 2-(2'-hydroxy-5'-acryloyloxyethylphenyl)-2H-benzotriazole, 2-(2'-hydroxy-5'-methacryloyloxyethylphenyl)-2H-benzotriazole, 2-(2'-hydroxy-5'-methacryloyloxyethylphenyl)-5-chloro-2H-benzotriazole, 2-(2'-hydroxy-5'-methacryloyloxypropylphenyl)-2H-benzotriazole, and 2-(2'-hydroxy-5'-methacryloyloxyethyl-3'-tert-butylphenyl)-2H-benzotriazole. From the perspectives of cost and operability, 2-(2'-hydroxy-5'-methacryloyloxyethylphenyl)-2H-benzotriazole is preferred. In this specification, (meth)acryloyl group is a general term for acryloyl group and methacryloyl group.
[0060] The content of constituent units from reactive ultraviolet absorbers in 100% by mass of the grafted polymer layer (A2) is preferably 0.01 to 5% by mass, more preferably 0.1 to 3% by mass.
[0061] The graft polymer layer (A2) is preferably obtained by graft copolymerization of a monomer mixture (a-2) comprising 70-99.5% by mass of alkyl methacrylate, 0.5-30% by mass of alkyl acrylate with 2 or more carbon atoms in the alkyl group, and 0-19% by mass of other vinyl monomers (wherein the total of alkyl methacrylate, alkyl acrylate, and other vinyl monomers is 100% by mass) through at least one polymerization step, in the presence of 5-90 parts by mass of crosslinked elastomer particles (A1). The total amount of crosslinked elastomer (A1) particles and monomer mixture (a-2) is 100 parts by mass.
[0062] In the manufacture of graft copolymer particles (A), especially during the graft copolymerization of monomer mixtures (a-2) in the presence of crosslinked elastomer (A1) particles, such as acrylate-based crosslinked elastomer (A1) particles, polymer components (free polymers) that are not graft-bonded to the acrylate-based crosslinked elastomer (A1) particles are sometimes produced. Such free polymers can be used as part or all of the substances constituting acrylic resins, which form the matrix phase of acrylic resin compositions and acrylic resin films.
[0063] For purposes such as controlling the molecular weight of the polymer, controlling the grafting rate of the crosslinked elastomer (A1) and the amount of free polymer not bonded to the crosslinked elastomer (A1), and controlling thermal stability by reducing the double bond ends of the polymer accompanying the disproportionation termination reaction during polymerization, a chain transfer agent can be added to the monomer mixture (a-2). Such a chain transfer agent can be the same as that used in the polymerization of the crosslinked elastomer (A1). The amount of chain transfer agent used is preferably 0 to 2 parts by mass or less, more preferably 0 to 0.5 parts by mass, relative to 100 parts by mass of the total monomer mixture (a-2).
[0064] The grafting rate of the monomer mixture (a-2) relative to the particles of the crosslinked elastomer (A1), i.e., the grafting rate of the graft copolymer particles (A), is preferably 5-250%, more preferably 10-200%, and even more preferably 20-150%. If the grafting rate is less than 5%, the acrylic resin film may experience reduced flexural whitening resistance, reduced transparency, or reduced elongation at tensile fracture, leading to a tendency for cracking during secondary molding. If the grafting rate exceeds 250%, the melt viscosity of the acrylic resin composition may easily increase during film molding, resulting in a tendency for reduced moldability of the acrylic resin film. In this specification, the grafting rate of the graft copolymer particles (A) can be determined by dissolving the powder of the graft copolymer particles (A) in methyl ethyl ketone, separating it into an insoluble portion and a soluble portion, and using the insoluble portion as the grafted portion, and then calculating it using the following formula.
[0065] Grafting rate (%) = (Mass of insoluble portion - Mass of cross-linked elastomer (A1)) / Mass of cross-linked elastomer (A1) × 100
[0066] The average particle size d (nm) of the acrylate-based crosslinked elastomer (A1) in the acrylic resin film preferably satisfies the relationship w (mass%) of the amount of multifunctional monomer used in the acrylate-based crosslinked elastomer (A1): 0.015d ≤ w ≤ 0.06d, more preferably 0.02d ≤ w ≤ 0.05d. If the amount of multifunctional monomer is within the range of the above relationship, it has the following advantages: the elongation of the acrylic resin film is not easily reduced during secondary molding, cracks are not easily generated during molding and cutting, the transparency is excellent, and stress whitening is not easily generated during bending or stretching deformation at room temperature (about 25°C), high temperature above the softening temperature of the acrylic resin film, or in the temperature range between room temperature and Tg of the crosslinked elastomer (A1), and thus the film is less prone to turbidity or whitening caused by moisture that permeates into the acrylic resin film due to contact with water.
[0067] The graft copolymer particle (B) also has a crosslinked elastomer (B1) as a rubber component, just like the graft copolymer particle (A). Typically, the graft copolymer particle (B) also has a graft polymer layer (B2) located on the surface side of the crosslinked elastomer (B1), just like the graft copolymer particle (A). That is, the graft copolymer particle (B) preferably has both a crosslinked elastomer (B1) and a graft polymer layer (B2).
[0068] The graft copolymer particles (B) can be made from roughly the same raw materials and manufacturing methods as the graft copolymer particles (A), except that their average particle size is larger than that of the graft copolymer particles (A). Preferably, the acrylate-based crosslinked elastomer (B1) particles have a concentric spherical multilayer structure in which a rigid or semi-rigid crosslinked resin layer is present inside the crosslinked elastomer layer. Examples of such rigid or semi-rigid crosslinked resin layers include rigid crosslinked methacrylate resin particles as shown in Japanese Patent Publication No. 55-27576 and crosslinked particles having a semi-rigid layer composed of methyl methacrylate-acrylate-styrene copolymers as shown in Japanese Patent Application Publication No. 4-270751 and WO2014 / 41803. By introducing such rigid or semi-rigid crosslinked resin layers, the transparency, resistance to flexural whitening, and resistance to flexural breakage of the graft copolymer particles (B), which have a larger particle size than the graft copolymer particles (A), can be improved.
[0069] The average particle size of the graft copolymer particles (B) is preferably 150–400 nm, more preferably 200–350 nm. Under external force on acrylic resin materials, graft copolymer particles (B) with a larger average particle size more effectively induce plastic deformation (cracking) in the acrylic resin phase surrounding the graft copolymer particles. Therefore, graft copolymer particles (B) have an excellent effect on imparting impact resistance and crack resistance to acrylic resin materials. On the other hand, compared with graft copolymer particles (A), graft copolymer particles (B) have poorer resistance to bending whitening and / or solvent whitening. Therefore, by adding a small amount of graft copolymer particles (B) to an acrylic resin composition containing acrylic resin and graft copolymer particles (A), for example, the following effects can be expected: (a) reducing the total content of the soft component relative to the acrylic resin film without reducing the surface hardness of the acrylic resin film and the laminate; (b) reducing the whitening properties of the acrylic resin film when external stress is applied, when coating with a coating liquid containing organic solvents, and / or during molding; and (c) effectively improving the crack resistance and secondary molding properties of the acrylic resin film and the laminate.
[0070] In this specification, the average particle size of graft copolymer particles (A) and graft copolymer particles (B) is the average particle size under volume basis (or mass basis if the density is uniform). It can be measured using a laser diffraction type particle size measuring device such as the Microtrac particle size distribution measuring device MT3000 manufactured by Nikkiso Co., Ltd. in the latex state, using the dynamic light scattering method.
[0071] There are no particular limitations on the manufacturing methods of graft copolymer particles (A) and graft copolymer particles (B), and well-known methods such as emulsion polymerization, microemulsion polymerization, suspension polymerization, and solution polymerization can be used. From the viewpoint of a large range of adjustments to the resin structure, emulsion polymerization is particularly preferred.
[0072] As initiators used in the emulsion polymerization of graft copolymer particles (A) and / or graft copolymer particles (B), known initiators such as organic peroxides, inorganic peroxides, and azo compounds can be used. Specifically, examples include organic peroxides such as tert-butyl hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, cumene hydroperoxide, benzoyl peroxide, lauroyl peroxide, alkyl percarbonate esters, and alkyl peroxide esters; inorganic peroxides such as potassium persulfate, sodium persulfate, and ammonium persulfate; and azo compounds such as azobisisobutyronitrile. One or more of these initiators can be used alone or in combination.
[0073] These initiators can be used as (a) thermally decomposable free radical polymerization initiators, or (b) these initiators, catalysts such as ferrous sulfate, and reducing agents such as sodium sulfite, sodium thiosulfate, sodium formaldehyde sulfoxylate, ascorbic acid, and hydroxypyruvic acid can be combined to form a redox polymerization initiator system. It should be noted that the catalyst can be used as a complex with sodium ethylenediaminetetraacetate-2-acetate to ensure water solubility.
[0074] The surfactants (also called emulsifiers) used in the emulsion polymerization of graft copolymer particles (A) and / or graft copolymer particles (B) are not particularly limited. Well-known surfactants can be widely used in emulsion polymerization. Preferred surfactants include, for example, anionic surfactants such as (a) sodium, potassium, and ammonium salts of alkyl sulfonic acids, alkylbenzene sulfonic acids, dialkyl sulfosuccinic acids (such as dioctyl sulfosuccinic acid), alkyl sulfuric acid, sodium fatty acids, polyoxyethylene alkyl ether acetic acid, polyoxyethylene alkyl ether phosphoric acid, alkyl phosphoric acid, alkyl ether phosphoric acid, alkyl phenyl ether phosphoric acid, and surfactantin, as well as (b) nonionic surfactants such as the reaction products of alkylphenols, aliphatic alcohols, and propylene oxide and / or ethylene oxide. These surfactants can be used alone or in combination of two or more.
[0075] Graft copolymer particles (A) or graft copolymer particles (B) obtained from emulsion polymerization can be separated and recovered from the latex of the latex containing graft copolymer particles (A) or graft copolymer particles (B) using known methods. For example, the graft copolymer particles can be coagulated by adding water-soluble electrolytes such as calcium chloride, magnesium sulfate, magnesium chloride, calcium acetate, sodium chloride, hydrochloric acid, acetic acid, and sulfuric acid to the latex, or by freezing the latex to separate and solidify the graft copolymer particles from the aqueous phase. The graft copolymer particles (A) or graft copolymer particles (B) can then be separated and recovered through filtration, washing, and drying of the solid components. Alternatively, the graft copolymer particles (A) or graft copolymer particles (B) can be separated and recovered through spray drying, freeze drying, or other treatments on the latex.
[0076] To reduce appearance defects and / or internal foreign matter in acrylic resin films, it is preferable to pre-filter the latex of graft copolymer particles (A) or graft copolymer particles (B) with a filter and / or screen before separating and recycling them, thereby removing environmental foreign matter and polymer contaminants that could cause defects.
[0077] As filters and screens, known filter and screen materials used in the filtration of liquid media can be used. The form of the filter and screen, the pore size, the filtration accuracy, and the filtration capacity can be appropriately selected according to the application, the type, size, and quantity of foreign matter to be removed. For example, the pore size and filtration accuracy of the filter and screen are preferably more than twice the average particle size of the graft copolymer particles (A) or (B).
[0078] The content of graft copolymer particles (A) in 100% by mass of the acrylic resin film is not particularly limited, but is preferably 1 to 80% by mass, more preferably 5 to 70% by mass, and even more preferably 10 to 60% by mass.
[0079] The content of graft copolymer particles (B) in 100% by mass of the acrylic resin film is not particularly limited, and can be appropriately adjusted within a preferred range according to the intended use without compromising the quality of the laminate of the present invention. However, from the viewpoint of suppressing stress whitening during the stretching or bending of the acrylic resin film and the clouding of the film after contact with moisture, it is preferable not to use excessive amounts, preferably 0 to 20% by mass, more preferably 0 to 10% by mass, and most preferably 0 to 5% by mass. Alternatively, the graft copolymer particles (B) may be completely absent.
[0080] <Other Ingredients>
[0081] Without prejudice to the purpose of this invention, the acrylic resin film (the acrylic resin composition constituting the acrylic resin film) may, as needed, include a thermoplastic resin that is at least partially compatible with the acrylic resin. Examples of such thermoplastic resins include styrene-based resins, polycarbonate resins, amorphous saturated polyester resins, olefin-methacrylic acid derivative resins, olefin-acrylic acid derivative resins, polyimide resins, polylactic acid resins, and PHBH (poly(3-hydroxybutyrate-co-3-hydroxyhexanoate)) resins. Examples of styrene-based resins include styrene-acrylonitrile resins, styrene-(meth)acrylic acid resins, styrene-maleic anhydride resins, styrene-N-substituted or unsubstituted maleimide resins, styrene-acrylonitrile-butadiene resins, and styrene-acrylonitrile-acrylate resins. Among these, the preferred thermoplastic resins are selected from styrene-based resins, polycarbonate resins, and polyimide resins, based on their excellent compatibility with acrylic resins and their ability to improve the flexural strength, solvent resistance, chemical resistance, and low moisture absorption of acrylic resin films. In this specification, (meth)acrylic acid is a general term for acrylic acid and methacrylic acid.
[0082] Furthermore, without prejudice to the purpose of one embodiment of the present invention, the acrylic resin film (the acrylic resin composition constituting the acrylic resin film) may include, as needed, conventionally known additives used in the acrylic resin film. Examples of such additives include antioxidants, ultraviolet absorbers (hereinafter also referred to as UVA), light stabilizers, light diffusing agents, matting agents, lubricants, colorants such as pigments and dyes, fibrous fillers, anti-blocking agents composed of organic and / or inorganic particles, infrared reflectors composed of metals and / or metal oxides, plasticizers, and antistatic agents. Additives are not limited to these. Without prejudice to the purpose of one embodiment of the present invention, or to enhance the effect of one embodiment of the present invention, these additives may be used in any amount depending on the type of additive.
[0083] <Properties of Acrylic Resin Films>
[0084] The glass transition temperature (Tg) of the acrylic resin film is preferably below 145°C, more preferably below 140°C, further preferably below 135°C, and particularly preferably below 130°C. If the glass transition temperature of the acrylic resin film is below 145°C, it has the advantage of being able to be molded without increasing the molding temperature and suppressing crack formation during molding. Furthermore, the lower limit of the glass transition temperature of the acrylic resin film is not particularly limited; from the viewpoint of preventing printing misalignment during drying and improving reliability, it is preferably, for example, above 100°C. More specifically, the glass transition temperature of the acrylic resin film can be 100–145°C, 100–140°C, 100–135°C, or 100–130°C. In this specification, the glass transition temperature of the acrylic resin film is determined by the method described in the examples.
[0085] The thickness of the acrylic resin film is not particularly limited, but is preferably 50–500 μm, more preferably 75–350 μm, even more preferably 80–300 μm, and particularly preferably 100–300 μm. If the thickness of the acrylic resin film is within the above range, it has the following advantages: the film has sufficient stretchability, excellent handling, and excellent appearance after being laminated onto the resin substrate during molding. In this specification, the thickness of the acrylic resin film is determined by the method described in the examples.
[0086] From the viewpoint of excellent scratch resistance, the pencil hardness of the acrylic resin film, as determined according to JIS K 5600-5-4, is preferably 2B or higher under a 500g load, more preferably B or higher, and particularly preferably HB or higher.
[0087] <Method for Manufacturing Acrylic Resin Films>
[0088] Acrylic resin films can be manufactured using known processing methods. Specific examples of known processing methods include melt processing, calendering, compression molding, and solvent casting. Examples of melt processing methods include blow molding and T-die extrusion. In solvent casting, for instance, after dissolving and dispersing an acrylic resin composition in a solvent, the resulting dispersion (solution) is cast into a film onto a strip substrate. Then, the solution is allowed to evaporate from the cast film-like solution, thereby obtaining an acrylic resin film.
[0089] Among these methods, solvent-free melt processing is preferred, with T-die extrusion and calendering being particularly preferred. Melt processing offers fewer limitations on film thickness, enables high-productivity production of films with excellent surface properties, reduces the environmental and operational burden of solvents, and lowers manufacturing costs.
[0090] When an acrylic resin composition is molded into a film by melt processing or solvent casting, from the viewpoint of improving the appearance quality of the acrylic resin film, it is preferable to use filtration with a filter or screen to remove environmental foreign matter, polymer dirt, and degraded resin from the acrylic resin composition that are the cause of appearance defects and internal foreign matter in the acrylic resin film.
[0091] When manufacturing membranes via melt processing, the acrylic resin composition can be filtered at any of the following times: during the melt mixing of the acrylic resin composition after combining raw materials such as acrylic resin and graft copolymer particles, and during the melt film forming process using a T-die. Alternatively, in the solvent casting method, the acrylic resin composition can be filtered after mixing the acrylic resin, graft copolymer particles (A), graft copolymer particles (B), and other components with the solvent and before casting to form a membrane.
[0092] As such filters and screens, known filters and screens can be used without particular restrictions, as long as they have heat resistance and durability corresponding to the melting processing conditions, as well as resistance to solvents and slurries used for casting.
[0093] When manufacturing acrylic resin membranes via melt processing, especially to obtain high-quality acrylic resin membranes, filters with large filtration capacity and low retention of molten resin, which are the causes of resin degradation and crosslinking that impair membrane quality, are preferred. For example, from the viewpoint of filtration efficiency and productivity, disc filters and pleated filters are preferred.
[0094] When manufacturing acrylic resin films using T-die extrusion, to improve film thickness accuracy, an automated die device can be used, for example, to online measure the film thickness distribution along the TD direction (perpendicular to the extrusion direction) of the extruded film and automatically adjust the die lip gap of the T-die in the extruded film based on this. By using appropriate control methods and applying an automated die, the thickness accuracy of acrylic resin films can be improved.
[0095] In the manufacture of acrylic resin films, when the film is being molded as needed, both sides of the molten film are simultaneously brought into contact (clamped) with a cooling roller or cooling belt, thereby obtaining a film with superior surface properties. In this case, it is preferable to bring the molten film into contact with a roller or cooling belt maintained at a temperature of -80°C or higher, preferably -70°C or higher, the glass transition temperature of the acrylic resin composition. As at least one of the rollers used for such clamping, it is more preferable to use, for example, a roller with an elastic metal sleeve disclosed in Japanese Patent Application Publication No. 2000-153547 and Japanese Patent Application Publication No. 11-235747, to transfer a roller mirror surface or a specific surface shape using low clamping pressure. As a result, a film with (a) low residual strain and excellent smoothness, and / or (b) a film with moderate surface roughness, excellent film surface lubricity, and less internal strain that suppresses adhesion between films can be obtained.
[0096] Alternatively, depending on the purpose, uniaxial or biaxial stretching can be performed after the membrane is formed. Uniaxial or biaxial stretching can be carried out using known stretching apparatus. Biaxial stretching can be performed in known forms such as successive biaxial stretching, simultaneous biaxial stretching, or longitudinal stretching followed by transverse stretching to suppress membrane bowing.
[0097] Furthermore, depending on the application requirements, one or both sides of the acrylic resin film can be endowed with any surface shape, such as fine lines, prisms, concave and convex shapes, three-dimensional decorations, matte surfaces, rough surfaces with a certain surface roughness, and knurling towards the film ends. Such surface shapes can be achieved using known methods. For example, one method involves clamping both sides of the molten film immediately after extrusion or the formed film fed from the feeding device with two rollers or belts having a surface shape on at least one surface, thereby transferring the surface shape of the transfer rollers.
[0098] (Hard coating)
[0099] The hard coating is formed from a cured resin composition comprising a urethane acrylate resin and a hindered amine light stabilizer having reactive functional groups. Specifically, the hard coating is formed by laminating the curable resin composition comprising a urethane acrylate resin and a hindered amine light stabilizer having reactive functional groups onto the surface of an acrylic resin film and then curing it. The hard coating may be laminated on one side or both sides of the acrylic resin film. The curable resin composition for the hard coating does not require large-scale heating equipment; from the viewpoint of fast curing and excellent cost, it preferably has active energy curing properties, and more preferably, the urethane acrylate resin has active energy curing properties.
[0100] In the laminates of one or more embodiments of the present invention, it is required that the hard coating has a high crack elongation while improving surface hardness. This prevents breakage or significant whitening during secondary molding of the laminate into a resin molded body, which would otherwise occur during stretching, bending, or other processing. However, generally, in hard coatings, the cured product of a curable resin composition containing a curable resin suppresses surface deformation relative to external stress through high cross-linking and / or the presence of fillers with high hardness, thereby exhibiting surface hardness and scratch resistance. Surface hardness and scratch resistance are opposite properties to deformability and tensile strength, making it difficult to achieve both simultaneously in hard coatings.
[0101] In order to impart high tensile strength during secondary molding while maintaining the surface hardness of the hard coating, the curing resin used in the hard coating can be improved, for example, by methods (1) to (3) below. In the hard coating, any one of the methods (1) to (3) can be used alone, or can be used in combination as appropriate. It should be noted that the hard coating can be made of a commercially available curing resin composition containing a urethane acrylate resin that can impart high tensile strength during secondary molding while maintaining the surface hardness of the hard coating.
[0102] (1) The glass transition temperature of the curing resin (specifically, urethane acrylate resin) is designed to be between room temperature (20±5°C) and secondary molding temperature (e.g., about 110 to 140°C), resulting in a design that is hard at room temperature and can soften and deform at the secondary molding temperature. As a result, the cured product (hard coating) of this curing resin exhibits high surface hardness at room temperature and high tensile strength during secondary molding.
[0103] (2) The design incorporates multiple curable resins with different structures, resulting in a non-uniform cross-linking structure after curing. This structure includes regions with high cross-linking density and regions with low cross-linking density and large plastic deformation, creating a non-uniform microstructure. Consequently, the cured resin exhibits high surface hardness due to the high cross-linking density region, while the low cross-linking density region deforms during secondary molding, resulting in high tensile strength.
[0104] (3) Incorporating resin components with low crosslinking degree or non-crosslinking and / or low elastic modulus into the curable resin. As a result, after the curable resin is cured, a structure is formed in which fine regions (structural domains) with low crosslinking degree or non-crosslinking and / or low elastic modulus are dispersed in the curable resin phase with high crosslinking density. Thus, the surface hardness is maintained to a certain extent in the cured product (hard coating) of the curable resin, and deformability and tensile properties are imparted. Examples of resin components with low crosslinking degree, non-crosslinking, or low elastic modulus include (a) thermoplastic resins such as thermoplastic methacrylate resin, styrene-acrylonitrile resin, aliphatic polycarbonate resin, aromatic polycarbonate resin, polyester resin, phenoxy resin, acylated cellulose resin, fluororesin, and polyurethane resin; (b) thermoplastic elastomer materials such as crosslinked or non-crosslinked soft resins such as acrylic rubber, silicone rubber, hydrogenated styrene-butadiene rubber, acrylonitrile-butadiene rubber, olefin rubber, and polyurethane rubber, as well as polyester, polyurethane, acrylic, olefin, styrene, silicone, and fluororesin materials, which may have reactive functional groups as needed; and (c) core-shell rubber particles on which thermoplastic resins are grafted onto the surface of crosslinked rubber particles.
[0105] <Carbamate acrylate resin>
[0106] Uracarbamate acrylate resins can be obtained, for example, by mixing polyols, polyisocyanates, and hydroxyl-containing (meth)acrylates, utilizing the reaction between the isocyanate groups and the hydroxyl groups to form urethane bonds. In this specification, (meth)acrylate is a general term for acrylates and methacrylates.
[0107] Alternatively, urethane acrylate resins can also be obtained by reacting a polyol with a polyisocyanate, causing the isocyanate groups at the ends or side chains of the resulting polyurethane compound to react with hydroxyl-containing (meth)acrylates, forming (meth)acryloyl groups at the ends or side chains. In this specification, (meth)acryloyl group means containing both methacryloyl and acryloyl groups.
[0108] The various properties of urethane acrylate resins can be appropriately adjusted, including molecular weight, composition, main chain structure (straight or branched), and number of functional groups, depending on the structure of the polyol, the type of polyisocyanate, and the number of acryloyl or methacryloyl groups (CH2=CH-CO- or CH2=C(CH3)-CO-) derived from hydroxyl-containing (meth)acrylates. There are no particular limitations. Further examples of urethane acrylate resins include commercially available urethane acrylate resins as UV-curable hard coatings.
[0109] As a polyisocyanate, any compound containing two or more isocyanate groups is acceptable, without particular limitations. Examples of polyisocyanate compounds include 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 1,3-phenylenediamine diisocyanate, 1,4-phenylenediamine diisocyanate, 1,5-naphthalene diisocyanate, m-phenylene diisocyanate, p-phenylene diisocyanate, 3,3'-dimethyl-4,4'-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate, 4,4'-diphenylmethane triisocyanate, 3,3'-dimethylphenylene diisocyanate, 4,4'-biphenylene diisocyanate, 1,6-hexane diisocyanate, isophorone diisocyanate, methylene bis(4-cyclohexyl) isocyanate, 2,2,4-trimethylhexamethylene diisocyanate, and bis(2-ethyl isocyanate). Fumarate, 6-isopropyl-1,3-phenyl diisocyanate, 4-diphenylpropane diisocyanate, toluidine diisocyanate, hydrogenated diphenylmethane diisocyanate, hydrogenated diphenylmethylene diisocyanate, tetramethyl diphenylmethylene diisocyanate, 2,5-bis(methyl isocyanate)-bicyclo[2.2.1]heptane, 2,6-bis(methyl isocyanate)-bicyclo[2.2.1]heptane, trimethylolpropane adduct of triethylene diisocyanate, isocyanurate of triethylene diisocyanate, oligomer of diphenylmethane-4,4'-diisocyanate, biuret of hexamethylene diisocyanate, isocyanurate of hexamethylene diisocyanate, urea diketone of hexamethylene diisocyanate, isocyanurate of isophorone diisocyanate, etc. Among these, polyisocyanate compounds that do not contain an aromatic skeleton but have a saturated aliphatic or alicyclic skeleton are preferred because they provide a structure with superior weather resistance. Examples of such polyisocyanate compounds include 1,6-hexane diisocyanate, isophorone diisocyanate, methylene bis(4-cyclohexyl)isocyanate, 2,2,4-trimethylhexamethylene diisocyanate, hydrogenated diphenylmethane diisocyanate, hydrogenated diphenylmethylene diisocyanate, 2,5-bis(methyl isocyanate)-bicyclo[2.2.1]heptane, and 2,6-bis(methyl isocyanate)-bicyclo[2.2.1]heptane. Furthermore, these polyisocyanates can be used alone or in combination of two or more.
[0110] Specific examples of polyols include ethylene glycol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 3-methyl-1,5-pentanediol, neopentanediol, 2-methyl-1,8-octanediol, cyclohexanediol, 1,4-cyclohexanediol, glycerol, pentaerythritol, dipentaerythritol, polycaprolactone diol, polyethylene glycol, polypropylene glycol, polytetramethylene diol, polyester diol, polycarbonate diol, polyurethane diol, bisphenol compounds, biphenol compounds, norbornyl diol, dicyclopentanediol, and adamantane diol. Among these, polyols that do not contain an aromatic backbone and have a saturated aliphatic or alicyclic backbone are preferred because they provide structures with superior weather resistance. These polyols can be used alone or in combination of two or more.
[0111] There are no particular limitations on hydroxyl-containing (meth)acrylates. For example, in addition to 2-hydroxyethyl acrylate and 2-hydroxyethyl methacrylate, compounds with at least one hydroxyl group and an olefinic unsaturated bond, such as 2-hydroxypropyl methacrylate, 4-hydroxybutyl acrylate, polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, trimethylolpropane mono(meth)acrylate, trimethylolpropane di(meth)acrylate, allyl alcohol, ethylene glycol allyl ether, glycerol (mono, die)allyl ether, N-hydroxymethyl (meth)acrylamide, etc., or (b) mixtures thereof, may be added as needed.
[0112] To promote the reaction between the isocyanate group and the hydroxyl group of the isocyanate component, an organotin-based carbamate catalyst can be used. Any catalyst commonly used in carbamate reactions can be used as an organotin-based carbamate catalyst, such as dibutyltin dilaurate, dibutyltin diacetate, dibutyltin dialkylmaleate, tin stearate, and tin octoate.
[0113] In one or more embodiments of the present invention, as at least a part of the curable resin composition for hard coating, a commercially available curable resin composition comprising urethane acrylate resin can be used. Examples of such commercially available products include, for instance, "Z-607-27L" manufactured by Aica Industries, Ltd., "Beamset 1200W" manufactured by Arakawa Chemical Industries, Ltd., "Acryt 8UX-116A" manufactured by Taisei Fine Chemicals Co., Ltd., "NXD-004AP" manufactured by Nippon Haku Coatings Co., Ltd., "P-5820TAH-1" and "P-5820TA-20J" manufactured by Daido Chemical Industries, Ltd., and "Lioduras MOL7200" manufactured by TOYOCHEM Co., Ltd. These commercially available curable resin compositions containing urethane acrylate resins also exhibit high elongation after curing, thus allowing for further improvement in the crack elongation of laminates at 120°C through their use.
[0114] <Light stabilizers>
[0115] The curable resin composition for hard coatings contains a light stabilizer. By including a light stabilizer, the hard coating's stability against ultraviolet and light degradation is improved, suppressing weathering degradation such as cracking and peeling on the surface of the resin molded body covered by the laminate containing the hard coating in outdoor or indoor sunlight exposure, or in its intended application.
[0116] The curable resin composition for hard coatings includes a hindered amine light stabilizer (hereinafter also referred to as "reactive HALS") having at least a reactive functional group as a light stabilizer. In the reactive HALS, the reactive functional group only needs to be reactive with the urethane acrylate resin; examples include functional groups having olefinic double bonds. More specifically, it is preferable to include one or more selected from methacryloyl, acryloyl, vinyl, and allyl groups, and more preferably, it includes one or more selected from methacryloyl and acryloyl groups. Furthermore, the substituent on the nitrogen atom of the amine functional group can be hydrogen, or it can be a substituent such as alkyl, phenyl, benzyl, alkoxy, acyl, or acyloxy groups, such as methyl, ethyl, and propyl. Because the hindered amine light stabilizer has a reactive functional group, when the urethane acrylate resin is cured, the hindered amine light stabilizer molecule reacts with the urethane acrylate resin and is introduced into the cured product forming the hard coating in a chemically bonded state. Therefore, even in outdoor exposure environments, the transfer and loss of hindered amine light stabilizers from the surface of the hard coating are inhibited, thereby suppressing the weathering degradation of the hard coating for a longer period of time.
[0117] Examples of reactive HALS include 4-(meth)acryloyloxy-2,2,6,6-tetramethylpiperidine, 4-(meth)acryloami-2,2,6,6-tetramethylpiperidine, 4-(meth)acryloyloxy-1,2,2,6,6-pentamethylpiperidine, 4-(meth)acryloami-1,2,2,6,6-pentamethylpiperidine, 4-cyano-4-(meth)acryloami-2,2,6,6-tetramethylpiperidine, and 4-barbituric acid. Crotonyloxy-2,2,6,6-tetramethylpiperidine, 4-crotonylamino-2,2,6,6-tetramethylpiperidine, 1-(meth)acryloyl-4-(meth)acryloylamino-2,2,6,6-tetramethylpiperidine, 1-(meth)acryloyl-4-cyano-4-(meth)acryloylamino-2,2,6,6-tetramethylpiperidine, and 1-crotonyl-4-crotonyloxy-2,2,6,6-tetramethylpiperidine, etc., but not limited to these. These reactive HALS can be used alone or in combination of two or more.
[0118] As reactive HALS, commercially available products such as 1,2,2,6,6-pentamethyl-4-piperidin methacrylate (trade name "Adekastab LA-82" manufactured by ADEKA Co., Ltd. or "FA-711MM" manufactured by Hitachi Chemical Co., Ltd.) and 2,2,6,6-tetramethyl-piperidin methacrylate (also known as 4-methacryloyloxy-2,2,6,6-tetramethylpiperidin, trade name "Adekastab LA-87" manufactured by ADEKA Co., Ltd. or "FA-712HM" manufactured by Hitachi Chemical Co., Ltd.) can be used.
[0119] The curable resin composition for hard coating preferably contains 1 to 10 parts by weight of reactive HALS relative to 100 parts by weight of urethane acrylate resin, more preferably 1.5 to 6 parts by weight, and even more preferably 2 to 4 parts by weight. The inclusion of 1 part or more of reactive HALS improves long-term weather resistance. Furthermore, if the reactive HALS content is 10 parts by weight or less, weather resistance can be improved without compromising the quality of the hard coating.
[0120] In addition to reactive HALS, the curable resin composition for hard coatings may, as needed, contain other light stabilizers such as hindered amine light stabilizers (hereinafter also referred to as HALS) that do not have reactive functional groups. Examples of HALS include bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate, bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate, methyl(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate, and 2,4-bis[n-butyl-N-(1-cyclohexyloxy-2,2,6,6-tetramethylpiperidin-4-yl)amino]-6-(2-hydroxyethylamine)-1,3,5-triazine. At this point, from the viewpoint of further improving weather resistance without exudation or curing hindrance during the curing of the hard coating, the curable resin composition for the hard coating may contain a total of 1 to 10 parts by weight of light stabilizer, or 1.5 to 6 parts by weight, or 2 to 4 parts by weight, relative to 100 parts by weight of urethane acrylate resin.
[0121] <Other Ingredients>
[0122] In addition to urethane acrylate resins and light stabilizers, hard coating curable resin compositions may also contain other components. These other components may include, for example, monomers, oligomers, resins, or mixtures thereof having free radical reactive functional groups, such as (meth)acrylate compounds, epoxy acrylate monomers, polyester acrylates, and polyacrylates. Furthermore, urethane acrylate resins may be used in combination with compositions, for example, hydrolytic condensates containing (a) di- to tetrafunctional silane compounds, and / or (b) monomers, oligomers, resins, or mixtures thereof having cationic and / or anionic curable functional groups such as epoxy and oxetyl groups. These other components may be used individually or in combination of two or more.
[0123] There are no particular restrictions on (meth)acrylate compounds as long as they have at least one (meth)acryloyl group. Specifically, examples include alicyclic (meth)acrylates such as alkyl (meth)acrylates, aryl (meth)acrylates, phenoxyethyl (meth)acrylate, and isobornyl (meth)acrylate; and polyfunctional (meth)acrylates such as polyalkylene glycol di(meth)acrylate, dipentaerythritol hexa(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, pentaerythritol tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, hexanediol di(meth)acrylate, and diethylene glycol di(meth)acrylate. They can be used alone or in mixtures of two or more. As (meth)acrylate compounds, examples include commercially available products as UV-curable hard coatings.
[0124] There are no particular limitations on the monomers used in epoxy acrylate systems. Specifically, examples include glycidyl methacrylate, β-methyl glycidyl methacrylate, 3,4-epoxycyclohexyl methyl methacrylate, and vinylcyclohexene monoxide (i.e., 1,2-epoxy-4-vinylcyclohexane).
[0125] Known methods can be used to cure the resin layer (curable resin composition) during the formation of a hard coating. As a curing method, irradiation with active energy rays, such as ultraviolet light or electron beams, is preferred. When curing is performed by ultraviolet irradiation, a photopolymerization initiator can be used.
[0126] Specific examples of photopolymerization initiators include acetophenone, benzophenone, benzoyl methyl ether, benzoyl ethyl ether, benzoin isopropyl ether, benzoin isobutyl ether, bibenzyl, 1-hydroxy-cyclohexyl-phenyl-one, 2,2-dimethoxy-2-phenylacetophenone, tetramethylthiuram monosulfide, tetramethylthiuram disulfide, thioxanthone, 2-chlorothiuram, 2-methylthiuram, and 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinylpropane-1-one compounds. Among these, 1-hydroxy-cyclohexyl-phenyl-one is preferred from the viewpoint of excellent compatibility with urethane acrylate resins.
[0127] A curable composition can be applied to one or both sides of an acrylic resin film, allowing the resin layer (coated film) composed of the curable composition to cure and form a hard coating. In this case, various known leveling agents and antifouling agents can be incorporated into the curable composition for purposes such as improving coatability, scratch resistance after curing, stain resistance, and smoothness. As leveling agents and antifouling agents, various compounds such as fluorine-based, acrylic-based, and silicone-based compounds, as well as their adducts or mixtures, can be used. These leveling agents and antifouling agents may contain functional groups that are reactive with urethane acrylate resins. The amount of leveling agent and antifouling agent is not particularly limited; for example, it may be 0.03 to 3.0 parts by weight relative to 100 parts by weight of the curable composition.
[0128] When a hard coating is formed by applying a curable composition to one or both sides of an acrylic resin film and allowing the film to cure, various additives such as UV absorbers, defoamers, antioxidants, light diffusing agents, matting agents, antifouling agents, lubricants, colorants such as pigments and dyes, organic particles, inorganic particles, and antistatic agents may be added to the curable composition as needed. Additives are not limited to these.
[0129] Furthermore, without prejudice to the purpose of this invention, the curable resin composition for hard coatings may contain inorganic particles. There are no particular limitations on the inorganic particles; examples include silica, alumina, titanium dioxide, zinc oxide, zirconium oxide, graphene, nano-carbon, carbon black, nano-diamond, mica, barium titanate, boron nitride, metallic silver, and metallic copper. These particles can be used without surface treatment. However, to control the dispersion state and maintain good tensile strength, surface treatment can be performed beforehand using known methods to appropriately control the affinity with the hard coating.
[0130] Furthermore, without prejudice to the purpose of this invention, from the viewpoint of improving the anti-glare properties of the laminate, the curable resin composition for the hard coating may contain particles. For particles incorporated into the hard coating for purposes such as imparting anti-glare properties, in order to obtain a balance of various properties such as desired anti-glare properties, image sharpness, glare, surface blackness, surface hardness, lubricity, and antistatic properties, the particle material, proportions, type of dispersion solvent, particle size, dispersed particle size, thickness of the hard coating, relative refractive index difference with the hard coating substrate, and affinity or reactivity of the particle surface with the hard coating substrate or solvent, etc., can be appropriately adjusted within the scope of known techniques without impairing the effects of this invention.
[0131] As for the material of the particles used in conjunction with the hard coating, there are no particular limitations as long as it can improve the anti-glare properties of the laminate without compromising the purpose of this invention. For example, inorganic particles and / or organic particles can be used. Examples of inorganic particles include silica, alumina, glass beads, glass sheets, mica, clay, titanium dioxide, zinc oxide, zirconium oxide, and metal particles. Examples of organic particles include, for example, cross-linked organic resin particles whose main component is selected from (meth)acrylate alkyl ester units, aromatic vinyl units, and siloxane units with organic functional groups, as well as core-shell type multilayer resin particles. From the viewpoint of easy availability and easy design of anti-glare properties according to the application, the particles are preferably selected from one or more of inorganic oxide particles (e.g., silica, alumina, titanium dioxide, zinc oxide, and zirconium oxide) and cross-linked organic resin particles (e.g., cross-linked silicone resin, cross-linked acrylic resin, and cross-linked aromatic vinyl resin), and more preferably from one or more of silica, alumina, zirconium oxide, and cross-linked organic resin particles. Furthermore, from the viewpoint of balancing physical properties such as anti-glare, dispersibility, and surface hardness, it is particularly preferable to select one or more particles selected from silica, alumina, and cross-linked organic resin particles. Additionally, from the viewpoint of controlling dispersibility, silane coupling agents or reactive monomers with reactive substituents can be used to perform surface treatment and / or graft polymerization treatment on these particles using known methods such as plasma treatment or corona treatment. From the perspective of improving the interfacial adhesion between the particles and the hard coating, thereby improving particle dispersibility, cracking during stretching, and / or whitening, it is preferable that at least a portion of the particles contain reactive functional groups on their surface that are reactive with urethane acrylate resins. Examples of reactive functional groups that are reactive with urethane acrylate resins include (a) radical reactive functional groups such as vinyl and (meth)acryloyl groups, (b) ionic functional groups such as epoxy, oxetyl, hydroxyl, carboxyl, mercapto, isocyanate, hydroxyl and amino groups, and (c) moisture-curing functional groups such as silyl and alkoxysilyl groups.
[0132] In hard coatings, "particles" can be dispersed either as primary particles or as aggregates of multiple particles, depending on their primary particle size. The size of the region (dispersion domain) where these particles or their aggregates are distributed is defined as the "average dispersion size". Even particles with large primary particle sizes may have an average dispersion size that is the same as the primary (basic) particle size.
[0133] The average dispersed particle size of the particles (e.g., silica particles) is not particularly limited as long as the effects of the present invention are achieved; for example, it can be 0.1–50.0 μm, 0.2–25.0 μm, or 0.5–10 μm. In this specification, a cross-sectional photograph of a laminate measured at 200,000x magnification (1200 nm × 800 nm) using an electron microscope (Hitachi High-Technologies Corporation, H7650) was observed, and the arithmetic mean of the particle size of the 10 dispersed structural domains of the particles in the hard coating was calculated. The obtained value was taken as the average dispersed particle size of the particles in the hard coating.
[0134] The content of the aforementioned particles in the hard coating is not particularly limited as long as it can improve the anti-glare properties of the laminate without compromising the purpose of the present invention. For example, it can be 0.1 to 30.0% by mass, 0.5 to 20.0% by mass, or 1.0 to 15.0% by mass.
[0135] To impart suitable coatability to the curable composition, an organic solvent is typically used. There are no particular limitations on the organic solvent, as long as it can impart the desired coatability to the curable composition and form a hard coating with the desired thickness and properties. From the viewpoint of coatability and the drying properties of the formed resin layer (coating film), the boiling point of the organic solvent is preferably 50–150°C.
[0136] Specific examples of organic solvents include saturated hydrocarbons such as hexane; aromatic hydrocarbons such as toluene and xylene; halogenated hydrocarbons such as chloroform and dichloromethane; alcohols such as methanol, ethanol, isopropanol, and butanol; esters such as methyl acetate, ethyl acetate, and butyl acetate; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; and tetrahydrofuran, dichloromethane ... Ethers such as alkanes, propylene glycol monoethyl ether, methyl meltblown agent, and ethyl meltblown agent; amides such as N-methylpyrrolidone and dimethylformamide, etc. Organic solvents can be used alone or in combination of two or more.
[0137] When a curable composition is applied to one or both sides of an acrylic resin film, any method can be used without limitation. Examples of coating methods include reverse coating, gravure coating, bar coating, mold coating, spray coating, kiss coating, wire bar coating, and curtain coating. These coating methods can be implemented individually or in combination.
[0138] After the hard coating described above is applied to one or both sides of an acrylic resin film to form a resin layer (coated film), the organic solvent is removed from the coating film by drying and the resin layer is cured by active energy rays such as ultraviolet irradiation, thereby forming a hard coating.
[0139] The drying temperature for removing organic solvents from the coated resin layer is preferably 60–120°C, more preferably 70–100°C. If the drying temperature is too low, organic solvents may remain in the resin layer (coated film). In addition, if the drying temperature is too high, the flatness of the laminate (hard coating) may be damaged due to thermal deformation of the acrylic resin film.
[0140] The wavelength of the ultraviolet light irradiated during the curing of the resin layer (coating film) is preferably in the range of 200–400 nm. The cumulative ultraviolet (UV) light intensity is preferably, for example, 150–700 mJ / cm². 2 More preferably 180–500 mJ / cm 2 Further preferably 200–400 mJ / cm 2 If the cumulative light intensity of the aforementioned UV irradiation is within the above-mentioned range, a suitable hardness of the hard coating can be obtained while ensuring formability. For example, irradiation devices for ultraviolet light exposure can be (a) light sources such as high-pressure mercury lamps, low-pressure mercury lamps, metal halide lamps, electrodeless lamps, and excimer lamps, and / or (b) irradiation devices equipped with pulsed or continuous laser sources such as argon ion lasers and helium-neon lasers.
[0141] Furthermore, in order to further improve the surface hardness, chemical resistance, weather resistance, etc. of the resin molded body on which the laminate of the present invention is disposed, the laminate can be further subjected to irradiation with active energy rays such as ultraviolet light after secondary molding of the laminate using vacuum and / or compressed air molding, or at least a portion of the resin molded body on which the laminate is disposed can be further subjected to such irradiation.
[0142] (Layered structure)
[0143] In one or more embodiments of the present invention, such as Figure 1 As shown, the laminate 1 comprises an acrylic resin film 2 and a hard coating layer 3 laminated on one side of the acrylic resin film 2. Alternatively, although not shown, the hard coating layer may also be laminated on both sides of the acrylic resin film. Furthermore, the laminate may, as needed, include other functional layers laminated between the acrylic resin film and the hard coating layer and / or on the hard coating layer, without impairing the effects of the present invention. Additionally, other functional layers may be laminated on the side opposite to the hard coating layer.
[0144] As for other functional layers, there are no particular limitations, and previously known functional layers can be widely used. Examples include low-refractive-index layers, primer layers, high-refractive-index layers, adhesive layers, anti-glare layers, anti-fouling layers, anti-fingerprint layers, anti-scratch layers, anti-static layers, ultraviolet shielding layers, infrared shielding layers, surface texture layers, light diffusion layers, matte layers, polarizing layers, coloring layers, design layers, printing layers, embossing layers, conductive layers, gas barrier layers, and gas absorption layers. A laminate can combine two or more other functional layers. Furthermore, a single functional layer can perform two or more functions.
[0145] The crack elongation at 120°C is 100% or more. Therefore, when the laminate is stacked on a thermoplastic resin substrate and used to coat the thermoplastic resin substrate, especially when the laminate is shaped and laminated onto the substrate under heating using vacuum forming and pneumatic forming, or when the shaped laminate is placed on a mold surface and then injection molded to obtain a molded body, defects such as cracking and whitening of the laminate can be suppressed, and good secondary molding properties are achieved. The crack elongation at 120°C is preferably 110% or more, more preferably 120% or more, further preferably 130% or more, and particularly preferably 140% or more. In this specification, the crack elongation at 120°C can be determined by the method described in the examples.
[0146] From the perspective of excellent long-term weather resistance, the laminate is preferably designed so that the surface of the hard coating of the laminate does not crack even after accelerated weathering testing. The accelerated weathering test involves setting the hard coating side of the laminate as the light source side, using a xenon lamp as the light source, and an irradiance of 180 W / m². 2 Under conditions of (300-400 nm), 1000 cycles were performed for a total of 2000 hours, consisting of step 1 (102 minutes exposure time, black panel temperature 60±3°C, relative humidity 65±5% and no rainfall) and step 2 (18 minutes exposure time, tank temperature 38±3°C, humidity 95±5% and rainfall), totaling 120 minutes. Furthermore, the color difference ΔE between the laminate after the accelerated weathering test and the laminate before the accelerated weathering test is preferably 0.5 or less, more preferably 0.3 or less. Particularly preferably, even when the above-described accelerated weathering test is performed for 2000 hours under simulated direct sunlight, specifically with the filter configured to use quartz glass on the inner side and polysilicate #275 on the outer side, the surface of the hard coating of the laminate does not crack, and the color difference ΔE between the laminate after the accelerated weathering test and the laminate before the accelerated weathering test is more preferably 0.5 or less, and even more preferably 0.3 or less.
[0147] From the viewpoint of transparency, the haze (Hz) of the laminate is preferably 2.0% or less, more preferably 1.5% or less, even more preferably 1.0% or less, even more preferably 0.8% or less, and particularly preferably 0.4% or less. However, based on requirements for appearance and other qualities, the introduction of matting agents, anti-glare agents, and other components into the acrylic resin film substrate and / or hard coating is not necessarily limited to this. In this specification, the haze can be measured by the method described in the examples.
[0148] In the laminate, from the viewpoint of having excellent surface hardness and improving the scratch resistance of the resin molded article using the laminate, the pencil hardness of the hard coating side is preferably B or higher under a 500g load, more preferably HB or higher, even more preferably F or higher, and particularly preferably H or higher.
[0149] From the viewpoint of excellent chemical resistance, it is preferable that the laminate shows no visual change when approximately 0.02 mL of isopropanol is dropped onto the surface of the hard coating and left at 23°C for 6 hours. Furthermore, from the viewpoint of excellent chemical resistance, it is preferable that the laminate shows no visual change when approximately 0.02 mL of acetone is dropped onto the surface of the hard coating and left at 23°C for 6 hours.
[0150] From the viewpoint of suppressing end whitening during finishing after molding, the Δhaze (ΔHz) of the laminate at 20% stretching at room temperature is preferably 3% or less, more preferably 2% or less, and even more preferably 1.5% or less. In this specification, the ΔHz of the laminate at 20% stretching at room temperature can be measured by the method described in the examples.
[0151] From the viewpoint of suppressing whitening during molding, the ΔHz of the laminate at 80% stretching at 120°C is preferably 3% or less, more preferably 2% or less, even more preferably 1% or less, more preferably 0.8% or less, and particularly preferably 0.4% or less. In this specification, the ΔHz of the laminate at 80% stretching at 120°C can be measured by the method described in the examples.
[0152] (Resin molded body)
[0153] The resin molded body comprises a thermoplastic resin substrate and a laminate, wherein at least a portion of the thermoplastic resin substrate is coated with the laminate, which is configured such that an acrylic resin film forms the side of the thermoplastic resin substrate. The laminate exhibits high elongation at crack at 120°C, thereby allowing the laminate to be used to coat at least a portion of the thermoplastic resin substrate having a non-planar curved shape and / or a three-dimensional shape, appropriately yielding a resin molded body with a three-dimensional shape. By coating a thermoplastic resin substrate within a resin molded body having various shapes, the laminate can impart various functionalities to the resin molded body, such as long-term weather resistance, scratch resistance, and chemical resistance.
[0154] The thermoplastic resin substrate may be composed of, for example, polycarbonate resin, acrylic resin, styrene resin (AS resin, ABS resin, MAS resin, styrene-maleimide resin, and styrene-maleic anhydride resin, etc.), saturated polyester resin, polyvinyl chloride resin, polyaryl ester resin, PPS resin, POM resin, polyamide resin, polylactic acid resin, acylated cellulose resin, and polyolefin resin, etc., having a bisphenol A, fluorene, or isosorbide-based backbone. From the viewpoint of excellent transparency, one or more resins selected from polycarbonate resin, acrylic resin, styrene resin, and amorphous polyolefin resin are preferred. From the viewpoint of good adhesion to the laminate, polycarbonate resin and / or acrylic resin are more preferred. From the viewpoint of high rigidity, high heat resistance, and high impact resistance, polycarbonate resin is further preferred.
[0155] Resin molded parts can be used as automotive interior materials, automotive exterior materials, optical components, appliance components, and building exterior materials. Due to the excellent long-term weather resistance of laminates, resin molded parts using these laminates can be appropriately used as automotive exterior materials and building exterior materials. As automotive exterior materials, there are no particular limitations; examples include door mirrors, windows, headlight covers, taillight covers, windshield components, weatherstripping, bumpers, bumper guards, side mudguards, body panels, spoilers, front longitudinal beams, pillar supports, wheel covers, center pillars, center trim pieces, side trim strips, door trim strips, and window trim strips. As building exterior materials, examples include wall panels, fences, roofs, door panels, and gable end cladding.
[0156] The method for manufacturing the resin molded body is not particularly limited as long as it is a molding method that can coat at least a portion of a thermoplastic resin substrate with an acrylic resin film side as the thermoplastic resin substrate side. Furthermore, the laminate can be appropriately formed with the aforementioned other functional layers before being laminated onto the substrate. Such a laminate can be used, for example, to manufacture a resin molded body with the laminate disposed on its surface by insert injection molding. Additionally, before insert injection molding, the laminate can be pre-formed as needed using methods such as vacuum forming, air-forming, and compression molding. Alternatively, so-called three-dimensional lamination molding can be performed, i.e., applying depressurization and / or pressure conditions to the laminate under heating to deposit the laminate on the surface of a thermoplastic resin substrate having at least a portion of a non-planar three-dimensional shape (curved shape) to create a resin molded body. Furthermore, the laminate can be heated and appropriately stretched, while being manually laminated onto the surface of a thermoplastic resin substrate to create a resin molded body.
[0157] Example
[0158] The present invention will now be described in more detail based on embodiments. The present invention is not limited to these embodiments. Unless otherwise specified, "parts" refers to "parts by mass" and "%" refers to "% by mass".
[0159] The measurement and evaluation methods used in the examples and comparative examples are described.
[0160] (Glass transition temperature)
[0161] A differential scanning calorimeter (DSC, Seiko Instruments, model "SSC-5200") was used. After a pre-adjustment process, the sample was temporarily heated to 200°C at a rate of 25°C / min, held for 10 minutes, and then cooled to 50°C at a rate of 25°C / min. DSC measurements were then performed during the heating process to 200°C at a rate of 10°C / min. The differential value (SSDC) was obtained from the resulting DSC curve, and the glass transition temperature was determined from its maximum point.
[0162] (Elongation at break under tension at 120℃)
[0163] An acrylic resin film was cut into 10mm (width) × 100mm (length) sections along the mechanical direction (MD) of the extruder forming process. These sections served as test specimens. Tensile testing was conducted using a Tensilon tensile testing machine (manufactured by Shimadzu Corporation, model "AG-2000D") equipped with a high-temperature bath set to 120°C. The conditions were: a preheating time of 2 minutes, a clamp spacing of 40mm, and a tensile speed of 200mm / min. The elongation at break was measured, and the average of the results from three specimens was taken as the elongation at break at 120°C.
[0164] (Crack elongation at 120℃)
[0165] A 10mm (width) × 100mm (length) section of the laminate was cut as a specimen. Tensile tests were conducted using a Tensilon tensile testing machine (manufactured by Shimadzu Corporation, model "AG-2000D") equipped with a high-temperature bath set to 120°C, under the conditions of a 2-minute preheating time, a 40mm clamp spacing, and a tensile speed of 200mm / min. The elongation at which cracks formed in the hard coating was measured, and the average of the test results obtained from measuring three specimens was taken as the crack elongation at 120°C.
[0166] (thickness)
[0167] The thickness of the acrylic resin film was measured using a PEACOCK dial gauge No. 25 (manufactured by Ozaki Manufacturing Co., Ltd.).
[0168] The thickness of the hard coating was measured using an F20 film thickness measurement system (manufactured by Filmetrics Co., Ltd.). The back side of the hard coating was blackened with a marker, and the refractive index of the acrylic resin film was 1.49 and the refractive index of the hard coating was 1.50 for measurement.
[0169] (Haze)
[0170] The haze was measured using an NDH4000 haze meter (manufactured by Nippon Denshoku Kogyo Co., Ltd.) in accordance with ISO 14782.
[0171] (ΔHz after 80% stretching at 120℃)
[0172] A 10mm (width) × 100mm (length) section of the laminate was cut as a specimen. Tensile tests were conducted using a Tensilon tensile testing machine (Shimadzu Corporation, AG-2000D) equipped with a high-temperature bath set to 120°C, under the following conditions: preheating time 2 minutes, clamp spacing 40mm, and tensile speed 200mm / min. The haze of the specimen before the tensile test was measured and recorded as the haze of the laminate before tensile testing. The haze of the specimen after 80% stretching was measured and recorded as the haze of the laminate after 80% stretching at 120°C. The difference between the haze of the laminate after 80% stretching at 120°C and the haze of the laminate before stretching was recorded as ΔHz after 80% stretching at 120°C.
[0173] The ΔHz of the laminate after 80% stretching at 120°C is equal to the haze of the laminate after 80% stretching at 120°C minus the haze of the laminate before stretching.
[0174] (ΔHz after 20% stretching at room temperature)
[0175] A 10mm (width) × 100mm (length) section of the laminate was cut as a specimen. A tensile test was performed using a Tensilon tensile testing machine (Shimadzu Corporation, model "AG-2000D") at 23°C, with a clamp spacing of 40mm and a tensile speed of 200mm / min, to achieve a 20% tensile strength. After the 20% tensile strength specimen was allowed to stand at 23°C for 12 hours, the haze was measured and recorded as the haze of the laminate after the 20% tensile strength test at room temperature. The haze of the specimen measured before the tensile test was recorded as the haze of the laminate before the tensile strength test. The difference between the haze of the laminate after the 20% tensile strength test at room temperature and the haze of the laminate before the tensile strength test was recorded as ΔHz after the 20% tensile strength test at room temperature.
[0176] ΔHz of a laminate after 20% stretching at room temperature = Haze of the laminate after 20% stretching at room temperature - Haze of the laminate before stretching
[0177] (Pencil hardness)
[0178] Pencil hardness was determined under a 500g load according to JIS K5600-5-4:1999.
[0179] (Accelerated weathering test)
[0180] An accelerated weathering test was conducted using a super-xenon weathering tester (manufactured by Suga Testing Equipment Co., Ltd., SX2D-75). The filter was constructed with quartz glass on the inside and polysilicate #275 on the outside to simulate direct sunlight. The laminated specimen (40mm × 50mm) was positioned with the hard coating side facing the light source, and 1000 cycles (2000 hours) of the following steps 1 and 2 (totaling 120 minutes) were performed.
[0181] Step 1: Exposure time 102 minutes, irradiance 180W / m² 2 (300~400nm), black panel temperature 60±3℃, relative humidity 65±5%, no rainfall.
[0182] Step 2: Exposure time 18 minutes, irradiance 180W / m² 2 (300~400nm), tank temperature 38±3℃, relative humidity 95±5%, with rainfall.
[0183] Visually inspect the surface of the hard coating on the sample after the accelerated weathering test to check for cracks. If no cracks are found, the sample is considered to have good long-term weather resistance.
[0184] Calculate the color difference between the laminate after the weathering test and the laminate before the weathering test. The color difference (ΔE) was measured using a spectrophotometer SE7700 (manufactured by Nippon Denshoku Kogyo Co., Ltd.) under the following conditions.
[0185] Mode: Transmitted, Light source: D65, Field of view: 2°, Measurement diameter: 28mm
[0186] (Chemical resistance test)
[0187] The sample, cut into 5cm×5cm squares, is placed horizontally with the hard coating side facing up. One drop (approximately 0.02mL) of isopropanol (hereinafter also referred to as IPA) is dropped onto it using a dropper. The sample is placed directly at room temperature (23°C) for 6 hours and the surface is observed. The chemical resistance is evaluated according to the following criteria.
[0188] Good: No changes in appearance
[0189] Slightly undesirable: leaving an outline
[0190] Defective: Appearance like it has dissolved
[0191] (Paint 1)
[0192] Methyl ethyl ketone (MEK) is incorporated into a highly tensile curable resin composition (containing urethane acrylate resin, manufactured by Daido Chemical Industry Co., Ltd., product name "P5820TA-20J", solid content 25%) with a solid content of 23%.
[0193] (Paint 2)
[0194] Methyl ethyl ketone (MEK) is incorporated into a low-stretch curing resin composition (containing urethane acrylate resin, manufactured by DIC Corporation, product name "ENS-102", solids content 99%) at a solids content of 23%.
[0195] (Example 1)
[0196] <Preparation of Acrylic Resin Films>
[0197] As the graft copolymer particles (A-1), multilayer structure particles (C4) with an average particle size of 85 nm, produced by the same method as Manufacturing Example 4 of Japanese Patent Application Publication No. 2020-147653, were used. As the acrylic resin (D-1), poly(methyl methacrylate) (manufactured by Sumitomo Chemical, brand name "Sumipex MG") was used. 100 parts of a resin mixture consisting of 38% graft copolymer particles (A-1) and 62% acrylic resin (D-1), 0.3 parts of a hindered phenolic antioxidant (manufactured by BASF, brand name "Irganox 1010"), and 1.5 parts of an ultraviolet absorber (benzotriazole ultraviolet absorber, manufactured by ADEKA, brand name "Adekastab LA-31") were mixed using a Henschel mixer. Next, using a vented co-rotating twin-screw extruder (manufactured by Toshiba Machine Co., Ltd., model "TEM58", L / D=41.7) with a barrel temperature adjusted to 190–250°C and an extrusion diameter of 58 mm, the material was melt-mixed at a screw speed of 150 rpm and a discharge rate of 180 kg / hr. The material was drawn into a wire bundle shape, cooled in a water bath, and then cut into granules using a granulator. The obtained granules were then melt-mixed using a single-screw extruder with a T-die and an extrusion diameter of 90 mm, with a barrel temperature set to 180–240°C and a discharge rate of 150 kg / hr. The material was discharged from the T-die at a die temperature of 240°C. While cooling and solidifying the material by contacting both sides with a metal casting roller with a temperature adjusted to 90°C and a touch roller with a flexible metal sleeve adjusted to 60°C, a film was formed and wound to obtain an acrylic resin film (D1) with a thickness of 75 μm.
[0198] <Creating Layered Bodies>
[0199] A hard coating curing resin composition was applied to one side of the obtained acrylic resin film using a bar coater. Then, after drying at 80°C for 2 minutes to evaporate the solvent, the film was irradiated with a UV irradiator under a nitrogen atmosphere (oxygen concentration ≤ 1%) with a cumulative UV light intensity of 460 mJ to form a hard coating (5 μm thick), resulting in a laminate. The hard coating curing resin composition used was a composition in which reactive HALS (manufactured by ADEKA Corporation, product name "Adekastab LA-82", hereinafter also referred to as LA82) was added to coating 1 in a ratio of 2 parts per 100 parts of the solid content of coating 1.
[0200] (Example 2)
[0201] As the graft copolymer particles (A-2), an acrylic graft copolymer (A) with an average particle size of 80 nm, prepared in the same manner as Reference Example 4 of Japanese Patent Application Publication No. 2004-137299, was used. As the acrylic resin (D-2), poly(methyl methacrylate) (manufactured by Sumitomo Chemical, Sumipex EX) was used. Using 100 parts of a resin mixture 2 consisting of 70% graft copolymer particles (A-2) and 30% acrylic resin (D-2), and with a discharge rate from the T-mold of 110 kg / hr, an acrylic resin film (D2) and a laminate were obtained in the same manner as in Example 1.
[0202] (Example 3)
[0203] As the graft copolymer particles (A-3), a multilayer acrylic resin with an average particle size of 130 nm was used, prepared in the same manner as "イ-3" in [Table 1] of Japanese Patent Application Publication No. 2015-7255. An acrylic resin film (D3) and a laminate were obtained in the same manner as in Example 1, except that 100 parts of a resin mixture 3 consisting of 40% graft copolymer particles (A-3) and 60% acrylic resin (D-2) were used.
[0204] (Example 4)
[0205] As the graft copolymer particles (A-4), graft copolymer particles (A) with an average particle size of 80 nm, prepared in the same manner as in Manufacturing Example 1 of International Publication No. 2019 / 181752, were used. As the graft copolymer particles (B-1), graft copolymer particles (B) with an average particle size of 230 nm, prepared in the same manner as in Manufacturing Example 12 of International Publication No. 2019 / 181752, were used. Using 100 parts of a resin mixture 4 consisting of 30% graft copolymer particles (A-4), 4% graft copolymer particles (B-1), and 66% acrylic resin (D-2), an acrylic resin film (D4) and a laminate were obtained in the same manner as in Example 1.
[0206] (Comparative Example 1)
[0207] As a curable resin composition for hard coating, coating 1 was used, and an acrylic resin film and laminate were obtained in the same manner as in Example 1.
[0208] (Comparative Example 2)
[0209] As a curable resin composition for hard coating, a composition in which a hydroxyphenyl triazine UV absorber (manufactured by BASF, trade name "Tinuvin 400", hereinafter also referred to as Tinuvin 400) was added to coating 1 in a manner of 2 parts per 100 parts of solid content of coating 1 was used. Otherwise, an acrylic resin film and a laminate were obtained in the same manner as in Example 1.
[0210] (Comparative Example 3)
[0211] As a curable resin composition for hard coating, a composition in which a hydroxyphenyl triazine UV absorber (manufactured by BASF, trade name "Tinuvin (registered trademark) 479", hereinafter also referred to as Tinuvin 479) was added to coating 1 in a manner of 2 parts per 100 parts of solid content of coating 1, otherwise, an acrylic resin film and a laminate were obtained in the same manner as in Example 1.
[0212] (Comparative Example 4)
[0213] As a curable resin composition for hard coating, a composition in which Tinuvin 400 and HALS (manufactured by BASF, trade name "Adekastab LA-81", hereinafter also referred to as LA81) were added to coating 1 in a manner of 2 parts and 1 part respectively relative to 100 parts of the solid content of coating 1, was used. Otherwise, an acrylic resin film and a laminate were obtained in the same manner as in Example 1.
[0214] (Comparative Example 5)
[0215] As a curable resin composition for hard coating, a composition in which LA81 was added to coating 1 in a manner of 2 parts per 100 parts of solids relative to coating 1 was used. Otherwise, an acrylic resin film and a laminate were obtained in the same manner as in Example 1.
[0216] (Comparative Example 6)
[0217] As a curable resin composition for hard coating, a composition in which LA82 was added to coating 2 in a manner that is 2 parts per 100 parts of solids relative to coating 2 was used. Otherwise, an acrylic resin film and a laminate were obtained in the same manner as in Example 1.
[0218] (Comparative Example 7)
[0219] As a curable resin composition for hard coating, coating 1 was used, and acrylic resin films and laminates were obtained in the same manner as in Example 2.
[0220] (Comparative Example 8)
[0221] As a curable resin composition for hard coating, a composition in which Tinuvin 400 was added to coating 1 in a manner of 2 parts per 100 parts of solids relative to coating 1 was used. Otherwise, an acrylic resin film and a laminate were obtained in the same manner as in Example 2.
[0222] (Comparative Example 9)
[0223] As a curable resin composition for hard coating, a composition in which Tinuvin 479 is added to coating 1 in a manner of 2 parts per 100 parts of solids relative to coating 1 is used. Otherwise, an acrylic resin film and a laminate are obtained in the same manner as in Example 2.
[0224] (Comparative Example 10)
[0225] As a curable resin composition for hard coating, a composition in which Tinuvin 400 and LA81 were added to coating 1 in a manner of 2 parts and 1 part respectively relative to 100 parts of the solid content of coating 1, was used. Otherwise, an acrylic resin film and a laminate were obtained in the same manner as in Example 2.
[0226] (Comparative Example 11)
[0227] As a curable resin composition for hard coating, a composition in which LA81 was added to coating 1 in a manner of 2 parts per 100 parts of solids relative to coating 1 was used. Otherwise, an acrylic resin film and a laminate were obtained in the same manner as in Example 1.
[0228] (Refer to Example 1)
[0229] An acrylic resin film prepared in the same manner as in Example 1 was used as Reference Example 1.
[0230] (See Example 2 for reference)
[0231] An acrylic resin film prepared in the same manner as in Example 2 was used as Reference Example 2.
[0232] In the examples and comparative examples, the crack elongation at 120°C, ΔHz after 80% stretching at 120°C, ΔHz after 20% stretching at room temperature, haze, pencil hardness, chemical resistance, and weather resistance of the laminate were measured as described above, and the results are shown in Tables 1 and 2 below. Additionally, in the examples and comparative examples, the thickness of the acrylic resin film, the tensile elongation at break and glass transition temperature at 120°C, and the thickness of the hard coating were measured as described above, and the results are shown in Tables 1 and 2 below. Tables 1 and 2 below also show the composition of the hard coating, with the proportions being parts by mass relative to 100 parts by mass of the solids content of the coating. It should be noted that in the reference example, the crack elongation at 120°C, ΔHz after 80% stretching at 120°C, ΔHz after 20% stretching at room temperature, haze, pencil hardness, chemical resistance, and weather resistance of the acrylic resin film were measured as described above, and the results are shown in the laminate column of Table 2 below. In Tables 1 and 2 below, "-" indicates that no measurements were taken.
[0233]
[0234]
[0235] As shown in Table 1 above, the laminates of Examples 1-4 exhibit a crack elongation rate of over 100% at 120°C, demonstrating good secondary molding properties. Furthermore, even after a 2000-hour accelerated weathering test, the hard coating of the laminates of Examples 1-4 did not crack, and the color difference was below 0.3, indicating good long-term weather resistance.
[0236] On the other hand, as shown in Tables 1 and 2 above, the laminates of Comparative Examples 1-5 and 7-11, which do not contain reactive HALS in their hard coatings, exhibited surface cracking after 1000 hours or 2000 hours of accelerated weathering testing, indicating poor long-term weather resistance. Furthermore, the laminate of Comparative Example 6, which uses a low-strength coating in its curable resin composition for hard coatings, showed a crack elongation of less than 100% at 120°C, indicating poor secondary molding properties.
[0237] This invention is not particularly limited, and may include, for example, the following embodiments.
[0238] [1] A laminate comprising an acrylic resin film and a hard coating layer laminated on at least one side of the acrylic resin film.
[0239] The above-mentioned acrylic resin film has a tensile elongation at break of over 200% at 120°C.
[0240] The aforementioned hard coating is formed from a cured resin composition comprising a urethane acrylate resin and a hindered amine light stabilizer having reactive functional groups.
[0241] The tensile crack elongation of the above-mentioned laminate at 120°C is over 100%.
[0242] [2] According to the laminate described in [1], after the accelerated weathering test, the surface of the hard coating of the laminate does not crack. The accelerated weathering test sets the hard coating side of the laminate as the light source side, uses a xenon lamp as the light source, and simulates direct sunlight at an irradiance of 180W / m. 2 Under conditions of (300-400nm), 1000 cycles (totaling 2000 hours) were performed, consisting of step 1 with an exposure time of 102 minutes, a black panel temperature of 60±3℃, a relative humidity of 65±5% and no rainfall, and step 2 with an exposure time of 18 minutes, a tank temperature of 38±3℃, a relative humidity of 95±5% and rainfall.
[0243] [3] According to the laminate described in [1] or [2], wherein the pencil hardness of the hard coating side of the laminate is B or higher under a 500g load, and there is no visual change when about 0.02 mL of isopropanol or acetone is dropped onto the surface of the hard coating and left at 23°C for 6 hours.
[0244] [4] The laminate according to any one of [1] to [3], wherein the color difference change ΔE of the laminate after the above-mentioned accelerated weathering test (a total of 2000 hours) is less than 0.5.
[0245] [5] The laminate according to any one of [1] to [4], wherein the above-mentioned urethane acrylate resin has active energy radiation curing properties.
[0246] [6] The laminate according to any one of [1] to [5], wherein the above-mentioned reactive functional group comprises one or more selected from methacryloyl and acryloyl.
[0247] [7] The laminate according to any one of [1] to [6], wherein the curable resin composition comprises a hindered amine light stabilizer having reactive functional groups in an amount of 1 to 10 parts by weight relative to 100 parts by weight of urethane acrylate resin.
[0248] [8] A resin molded body comprising a laminate as described in any one of [1] to [7] and a thermoplastic resin substrate, wherein at least a portion of the thermoplastic resin substrate is covered by the laminate configured such that an acrylic resin film is on the thermoplastic resin substrate side.
[0249] [9] The resin molded body according to [8], wherein the above-mentioned thermoplastic resin substrate has a three-dimensional shape.
[0250] The embodiments described above are not independent of each other and do not require excessive explanation; those skilled in the art can combine them appropriately. Furthermore, the constituent elements of different embodiments can be appropriately combined.
[0251] Symbol Explanation
[0252] 1-layer stack
[0253] 2. Acrylic resin film
[0254] 3. Hard coating.
Claims
1. A laminate comprising an acrylic resin film and a hard coating layer laminated on at least one side of the acrylic resin film. The acrylic resin film has a tensile elongation at break of over 200% at 120°C. The hard coating is formed from a cured resin composition comprising a urethane acrylate resin and a hindered amine light stabilizer having reactive functional groups. The tensile crack elongation of the laminate at 120°C is over 100%.
2. The laminated body according to claim 1, wherein, After undergoing the accelerated weathering test, the surface of the hard coating of the laminate did not crack. The accelerated weathering test involved setting the hard coating side of the laminate as the light source side, using a xenon lamp as the light source to simulate direct sunlight, with an irradiance of 180 W / m² at 300–400 nm. 2 Under these conditions, 1000 cycles (totaling 2000 hours) will be implemented, consisting of step 1 with an exposure time of 102 minutes, a black panel temperature of 60±3℃, a relative humidity of 65±5% and no rainfall, and step 2 with an exposure time of 18 minutes, a tank temperature of 38±3℃, a relative humidity of 95±5% and rainfall.
3. The laminated body according to claim 1, wherein, The hard coating side of the laminate has a pencil hardness of B or higher under a 500g load, and when approximately 0.02 mL of isopropanol or acetone is dropped onto the surface of the hard coating and left at 23°C for 6 hours, there is no visual change in appearance.
4. The laminated body according to claim 1, wherein, The color difference change ΔE of the laminate after the accelerated weathering test (a total of 2000 hours) is less than 0.
5.
5. The laminated body according to claim 1, wherein, The urethane acrylate resin has active energy radiation curing properties.
6. The laminate according to claim 1, wherein, The reactive functional group comprises one or more selected from methacryloyl and acryloyl.
7. The laminated body according to claim 1, wherein, The curable resin composition comprises 1 to 10 parts by weight of a hindered amine light stabilizer having reactive functional groups relative to 100 parts by weight of the urethane acrylate resin.
8. A resin molded body comprising a laminate according to any one of claims 1 to 7 and a thermoplastic resin substrate, wherein at least a portion of the thermoplastic resin substrate is covered by the laminate, said laminate being configured such that an acrylic resin film forms the thermoplastic resin substrate side.
9. The resin molded article according to claim 8, wherein, The thermoplastic resin substrate has a three-dimensional shape.
Citation Information
Patent Citations
JP1980027576B2
Imide polymer
JP1987089705A
Methacrylimide-containing polymer and resin composition containing the same
JP1990178310A
Impact-resistant methacrylic resin composition
JP1992270751A
Film for protecting polarizing film
JP1993119217A